The effect of coastal geometry on the location of peak surge (MAUSAM, 1982)
An attempt has been made to study the dynamic effect of a curving coast and the angle of incidence of the tropical cyclone track relative to shore-line on the location of the peak surge. The experiments have been performed by a numerical storm surge prediction model for the east coast of India.                                           Using a forcing wind-stress distribution representative of a severe cyclonic storm. with a core of hurricane winds, a comparison of the results is made for different tracks of a cyclone Striking at three different places along the east coast of India which have different type of coastal configurations, viz. .(i) almost straight line coast. Running approximately from Nagapatinam in the south to Ongole in the north, which is parallel to meridian. (ii) Crescent coast running from Nellore in the south to Masulipatnam in the north, which resembles the crescent of the moon and (iii) a slant coast. running approximately from Visakhapatnam in the south to Patadeep in the north, which is an almost straight line coast inclined to meridians. The results of the experiment show that the location of the highest surge is sensitive to the coastal geometry and the direction of motion of the storm relative to the coast.